MUTU SENSORI MI INSTAN YANG DIBUAT DARI SUBSTITUSI PATI SAGU DENGAN TEPUNG UBI JALAR UNGU - Betty ' '; Yusmarini ' '; Noviar ' Harun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The use ofpurple sweet potatoflouras an ingredientsubstitutionof sagostarchin making ofinstant noodlesis expected toimprove the colorandincrease thefiber contentof instant noodles. This study was uses acompletely randomized design(CRD) with 6treatments and 3 replicationsthatproduced18experimental units. The obtaineddata were statistically analyzed usingAnalysisofVariance(ANOVA). If theFcount is highthanor equal toFtable thencontinued withDNMRTtestatthe 5% level. Results of this study indicated that theuse ofpurple sweet potatofloursignificant effectof thecolor, taste andaroma ofinstant noodles, butdidn’t significantly effectof texture ofinstant noodles. Based onan overall assessment,the panelistslikeinstant noodlesof all treatments. The best treatment wasselected isSUP5(65% sagostarch, 25% purple sweet potatoflourand10% patin fish). Keywords: Sago starch, purple sweet potato flour, instan noodles.